THE PHENOMENON OF EMOTIONAL BURNOUT IN THE CONTEXT OF INTROVERSION AND EXTRAVERSION - Ergasheva Nargizakhon Аbdusattarovna (Bright Mind Publishing, 2025)
The article presents a psychological analysis of the phenomenon of emotional exhaustion occurring in modern life, examines the levels of adaptation to stress and emotional stability based on the concepts of temperament, introversion, and extraversion, and highlights the significance of individual approaches to managing emotional exhaustion based on the theories of Jung and Eysenck.
Keywords: Emotional exhaustion, temperament, introversion, extraversion, stress, psychological adaptation, personality typology, Carl Gustav Jung, Hans Eysenck, psychophysiological characteristics, individual approach.